2015
DOI: 10.3109/10799893.2015.1122040
|View full text |Cite
|
Sign up to set email alerts
|

Evodiamine inhibits the proliferation of leukemia cell line K562 by regulating peroxisome proliferators-activated receptor gamma (PPARγ) pathway

Abstract: Evodiamine, a quinolone alkaloid, is one of the major bioactive compounds of Evodia rutaecarpa Bentham (Rutaceae). It exhibits excellent biological activities, especially the anticancer activity. This study aims to investigate the effect of evodiamine on the proliferation of leukemia cell line K562 and to explore the underlying mechanism. The effect of evodiamine on K562 cells proliferation was analyzed by trypan blue dye exclusion assay and MTT assay. The expression levels of peroxisome proliferators-activate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…In addition, evodiamine is not toxic to human normal peripheral blood mononuclear cell (PBMC) [ 57 , 58 ]. In another study, peroxisome proliferator-activated receptor γ (PPARγ) signaling pathway was reported to be involved in the proliferation inhibition of evodiamine on K562 cells via inhibiting cyclin D1 and stimulating of p21, the important factors for the regulation of cell cycle progression [ 59 ]. Moreover, evodiamine decreased NF-κB activity and expressions of NF-κB-dependent antiapoptotic, proliferative, and metastatic genes in human myeloid leukemia KBM-5 cells, which indicated NF-κB might be another potential target of evodiamine for anti-leukemia therapy [ 60 ] ( Figure 3 ).…”
Section: Pharmacological Activitymentioning
confidence: 99%
“…In addition, evodiamine is not toxic to human normal peripheral blood mononuclear cell (PBMC) [ 57 , 58 ]. In another study, peroxisome proliferator-activated receptor γ (PPARγ) signaling pathway was reported to be involved in the proliferation inhibition of evodiamine on K562 cells via inhibiting cyclin D1 and stimulating of p21, the important factors for the regulation of cell cycle progression [ 59 ]. Moreover, evodiamine decreased NF-κB activity and expressions of NF-κB-dependent antiapoptotic, proliferative, and metastatic genes in human myeloid leukemia KBM-5 cells, which indicated NF-κB might be another potential target of evodiamine for anti-leukemia therapy [ 60 ] ( Figure 3 ).…”
Section: Pharmacological Activitymentioning
confidence: 99%
“…For example, berberine can inhibit the proliferation of cancer cell lines by interfering with cell proliferation [40] and inducing apoptotic cell death [41]. Evodiamine or quinolone alkaloid showed anti-cancer activities by inducing cell cycle blocking in the K562 erythroleukemic cell line [42], causing DNA damage in MCF-7 breast cancer cells [43], inducing apoptosis in U937 human leukemic cells [44], interfering with angiogenesis [45], and interfering with cell metastasis in Lewis lung carcinoma (LLC) and B16-F10 melanoma [46]. …”
Section: Discussionmentioning
confidence: 99%
“…Stimulation of cathecolamine secretion [2] Pain relief [3] Anti-inflammatory [4,5] Weight loss through increased thermogenesis (weight loss with EVO is a controversial issue which has not been fully clarified) [6][7][8] Vasodilation [9] Inhibitory effects on the synthesis of prostaglandin E2 (PGE2), this can be considered as part of its anti-inflamatory effects.…”
Section: Action Referencementioning
confidence: 99%
“…Another paragraph on the issue ANSES says: "The major alkaloids of Evodia, evodiamine and rutaecarpine, have modulatory effects on metabolizing enzymes, in particular cytochromes P450 CYP3A4, CYP1A2 and CYP1A1 (Ueng et al 2002; Wen et al 2014) [7] which metabolize many drugs". No other major adverse effects are described in this "opinion" of ANSES, and no other warnings are given.…”
Section: Action Referencementioning
confidence: 99%